2005
DOI: 10.1103/physrevb.71.205404
|View full text |Cite
|
Sign up to set email alerts
|

Theory of electric force microscopy in the parametric amplification regime

Abstract: We propose to use a parametric amplification regime for small charge or potential difference detection in electric force microscopy. First we give a simple method to accurately estimate the instability domains of the oscillating system. Then we establish general and fully analytical expressions of the parametric amplification gain, and discuss the optimal parameter values which must be used for voltage or charge detection. We show that even in conventional Kelvin probe force microscopy the parametric effect sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 29 publications
0
16
0
Order By: Relevance
“…This enhanced resolution in AM-KPFM with a near resonance excitation may be due to the parametric effect discussed in [18,19]. As the electrostatic interaction becomes large, the electrostatic force gradient term, which is usually neglected in AM-KPFM, begins to play a dominant role in the resulting amplitude response.…”
Section: Am-kpfm Mode Versus Fm-kpfm Modementioning
confidence: 99%
“…This enhanced resolution in AM-KPFM with a near resonance excitation may be due to the parametric effect discussed in [18,19]. As the electrostatic interaction becomes large, the electrostatic force gradient term, which is usually neglected in AM-KPFM, begins to play a dominant role in the resulting amplitude response.…”
Section: Am-kpfm Mode Versus Fm-kpfm Modementioning
confidence: 99%
“…͑9a͔͒, ͑2͒ the signal intensity of ⌬f at is often low because of limited bandwidth of the FM demodulator, ͑3͒ the large AC voltage bias necessary for high sensitivity can induce band bending on semiconductor samples, ͑4͒ very short tip-surface distances are required to obtain accurate values of , and ͑5͒ the measurement itself is extremely sensitive to lift height. It has also been demonstrated that KFM can be strongly affected by parametric amplification for tip-surface distances much larger than the onset of tapping, 48 making Eqs. ͑9a͒-͑9c͒ no longer valid.…”
Section: Kelvin Probe Versus Am-efmmentioning
confidence: 98%
“…ternal signal) and non-degenerate (where the pump is locked at a frequency distinct from that of the external signal) manifestations of parametric amplification in a variety of resonant microsystems, including torsional microresonators [4,5], electric force microscopes [6], optically-excited micromechanical oscillators [7], micro ring gyroscopes [8], MEMS diaphragms [9], coupled microresonators [10], and microcantilevers [11][12][13].…”
Section: Detc2007-35426mentioning
confidence: 99%